The domination over time and its discretisation - Abbasnezhad, Nazanin; Mehri-Takmeh, Javad; Vakili, Javad (Operations research and decisions, 2020)
Domination in graphs is well known and has been an extensively researched branch of graph theory. Since the variation over time is one of the important properties of real-world networks, we study the influence of time on the domination problem. In this paper, we introduce the domination over time problem, including time delay on arcs. Then, an optimal solution to its discretisation is obtained, which is the solution of the original problem.